NiMn layered double hydroxide as efficient electrocatalyst for oxygen evolution reaction and its application in rechargeable Zn- air batteries - Sumboja, Afriyanti (2020)
High performance catalyst for oxygen evolution reaction (OER) is in demand to improve the re-chargeability of Zn-air battery. In this work, atomically dispersed NiMn layered double hydroxides are prepared via simple hydrothermal synthesis and tested as an OER catalyst in rechargeable Zn-air batteries. NiMn layered double hydroxides with the optimized Ni:Mn molar feeding ratio have good crystallinity, big interlayer spacing, and large surface area, which are beneficial to enhance their catalytic activity. They are highly active and stable during OER, showing overpotential of 0.35 V, Tafel slope of 40 mV dec-1, and remarkable stability during 16 h of chronopotentiometry test. Rechargeable Zn-air batteries with NiMn layered double hydroxides as OER catalyst exhibit a low charge voltage of ≈2 V which are stable for up to 200 cycles. This study illustrates the platform to enhance catalytic activity of OER catalyst via fine-tuning the composition and physical properties of the materials and their application for rechargeable metal-air batteries.